Update of the mortality study of workers exposed to polychlorinated biphenyls (PCBs) in two Italian capacitor manufacturing plants / Aggiornamento dello studio di mortalità in lavoratori esposti a policlorobifenili (PCB) in due aziende italiane... - Pesatori, Angela Cecilia; Grillo, P; Consonni, D; Caironi, M; Sampietro, G; Olivari, Leonella; Ghisleni, Silvia; Bertazzi, P A (La Medicina del Lavoro, 2013)
Background: PCB carcinogenicity to humans is still controversial. Cohort mortality studies in PCB-exposed workers reported elevated risks for the following causes of death: liver, stomach, digestive, brain, prostate cancers and non-Hodgkin lymphoma. Objectives: The purpose of this study was to update as of December 2006 the mortality experience of two Italian cohorts of workers employed in the manufacture of capacitors impregnated with PCBs. Methods: Age-gender-and calendar period adjusted Standardized Mortality Ratios (SMRs) and 95% Confidence Intervals (CI) were calculated using regional rates. Analyses by duration of employment and time since first employment were performed. Results: Vital status was ascertained for 98.9% of the study subjects. Mortality from biliary tract cancer among males (SMR 3.91; 95%CI 1.47-10.41), digestive cancer “not otherwise specified” in the whole cohort (SMR 2.54; 95%CI 1.21-5.34), and brain cancer in Plant 1 (SMR 2.13; 95%CI 1.02-4.48), were significantly increased. Increased risks were also observed for Hodgkin’s and non-Hodgkin lymphoma. No linear associations between mortality and duration of employment or latency were observed for these cancers. Mortality from stomach cancer did not differ from expectation in the whole cohort, however an increasing risk with increasing duration of employment was detected (p for trend=0.02). Conclusions: The current update suggests possibly increased cancer risks in PCB-exposed workers, affecting in particular the digestive system, brain, and lymphohemopoietic tissue. However the limited sample size, the lack of clear trends with duration of employment or with latency period, preclude to derive definite conclusions about PCB exposure and the increased cancer risks.Aggiornamento dello studio di mortalità in lavoratori esposti a policlorobifenili (PCB) in due aziende italiane produttrici di trasformatoriIntroduzione: La cancerogenicità dei policlorobifenili (PCB) nell’uomo è tuttora controversa. Gli studi in coorti lavorative hanno riportato rischi aumentati per tumori del fegato, dello stomaco, dell’apparato digerente, dell’encefalo, della prostata e linfomi non-Hodgkin. Obiettivi: Scopo del presente studio è l’estensione del follow-up al Dicembre 2006 di una coorte di lavoratori in due aziende produttrici di trasformatori impregnati con PCB in Lombardia. Metodi: Sono stati calcolati i Rapporti Standardizzati di Mortalità (SMR) e gli Intervalli di confidenza al 95% (IC) utilizzando come riferimento i tassi della regione Lombardia. Risultati: Lo stato in vita è stato accertato per il 98,9% della coorte. Sono stati osservati incrementi significativi della mortalità  per tumori del tratto biliare nei maschi (4 casi, SMR 3,91; IC 95% 1,47-10,41), del digerente ”non altrimenti specificati” nell’intera coorte (7 casi, SMR 2,54; IC 95% 1,21-5,34), e dell’encefalo nella Ditta 1 (7 casi, SMR 2,13; IC 95% 1,02-4,48). Anche la mortalità per malattia di Hodgkin (4 casi) e linfomi non-Hodgkin (8 casi) è risultata aumentata. Non sono emersi chiari  andamenti della mortalità per durata dell’attività lavorativa o per latenza. Solo il tumore dello stomaco ha mostrato un incremento della mortalità all’aumentare della durata della attività lavorativa (p per il trend=0,02). Conclusioni: Lo studio ha evidenziato incrementi di rischio a carico dei tumori dell’apparato digerente, dell’encefalo e del tessuto linfoemopioietico. L’associazione tra esposizione a PCB e tali rischi rimane incerta per l’assenza di andamenti rilevanti con la durata dell’attività lavorativa e la latenza e il piccolo numero di casi.